Age in love : Shakespeare and the Elizabethan court - Vanhoutte, Jacqueline, 1968- (Early modern cultural studies (Lincoln, Neb.), 2019)
"Age in Love contributes to the ongoing debate about the emergence of a Tudor public sphere, building on the current interest in premodern constructions of aging and ultimately demonstrating that the Elizabethan court shaped Shakespeare's plays in unexpected and previously undocumented ways"--